ACT-11 CLINICAL BENEFIT OF ADD-ON BEVACIZUMAB FOR NEWLY DIAGNOSED GLIOBLASTOMA IN ELDERLY PATIENTS WITH UNRESECTABLE AND POOR PERFORMANCE STATUS. (3rd December 2022) - Tomoto, Kyoichi; Yamamoto, Yohei; Tanaka, Toshihide; Suzuki, Tomoya; Teshigawara, Akihiko; Takei, Jun; Koseki, Hirokazu; Mori, Ryosuke; Akasaki, Yasuharu; Murayama, Yuichi
Abstract: Background: Since phase 3 randomized clinical trials failed to show the benefit of bevacizumab(Bev) from the induction therapy, Bev was widely used for the recurrence glioblastoma(GBM) cases. Given that Bev treatment for newly diagnosed GBM(nd-GBM) is permitted only in Japan, we could confirm the appropriate usage and timing of Bev for the GBM patient clinically. Here, we report the clinical benefit of Bev for nd-GBM based on the retrospective cohort study. Methods: We retrospectively investigated 172 GBM patients who were treated with surgery, radiation therapy(RT) and temozolomide(TMZ) at our hospitals in 2006 to 2020. We classified with and without Bev patients for age, Karnofsky performance status(KPS) and extent of resection(EOR). Kaplan-Meier survival analysis was used to compare median overall survival(mOS) between patients who were treated with Bev simultaneously during Stupp regimen(S-Bev) and without Bev(NS-Bev). Results: Bev provided prolonged mOS in the elderly(>60 years old)(p<0.01), poor KPS(<70)(p=0.015) and low EOR(<90%)(p<0.01) groups. In addition, mOS was longer in S-Bev compared with NS-Bev in the elderly and low EOR groups, and there was statistically significant difference in low EOR group(p<0.01). S-Bev tended to prolong mOS in elder patients(p=0.06) and NS-Bev tended to prolong in young patients(p=0.31). Conclusion: Bev therapy commenced simultaneously with concurrent RT and TMZ might contribute to improve mOS for patients with high risk including the elderly, poor KPS and low EOR. Stratification based on risk factors including age and EOR might be effective for patients in whom Bev should be preferentially used as a first-line therapy.